Counteracting negative effects of salinity on Lepidium sativum L. seedlings by prepared biochar - Amira Mohamed Abd El-Sattar; Zeinab Ashour Shedeed (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Biochar is a carbon rich material that showed positive outcomes on plant growth and productivity enduring abiotic stresses. The objective of the present investigation is thus to determine the potential of biochar to mitigate the detrimental impacts of salinity in Lepidium sativum.